2008
DOI: 10.22621/cfn.v122i4.642
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Peripheral Populations of Great Basin Pocket Mice, <em>Perognathus parvus</em>, and Western Harvest Mice, <em>Reithrodontomys megalotis</em>, in Southern British Columbia

Abstract: The Great Basin Pocket Mouse (Perognathus parvus) and Western Harvest Mouse (Reithrodontomys megalotis) are two peripheral species occurring in the southern Okanagan Valley of British Columbia, Canada. Both species are listed as vulnerable to extirpation because of habitat loss, primarily due to conversion of natural habitat to agricultural uses and suburban expansion. Population dynamics of these two species were studied in three habitat types: old field, sagebrush, and pine forest. The Great Basin Pocket Mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This pattern was clear for P. parvus which inhabited the orchard-sagebrush margin to a significant degree, followed by the orchard-old field margin. Mean abundance per line was 3.9 times higher in the sage than old field margin; a similar magnitude of difference was reported for non-linear examples of these two habitats (Sullivan and Sullivan, 2008). Tattersall et al (2002) reported no difference in small mammal abundance or diversity when linear and nonlinear habitats in an agricultural setting were compared.…”
Section: Species At Risksupporting
confidence: 71%
See 2 more Smart Citations
“…This pattern was clear for P. parvus which inhabited the orchard-sagebrush margin to a significant degree, followed by the orchard-old field margin. Mean abundance per line was 3.9 times higher in the sage than old field margin; a similar magnitude of difference was reported for non-linear examples of these two habitats (Sullivan and Sullivan, 2008). Tattersall et al (2002) reported no difference in small mammal abundance or diversity when linear and nonlinear habitats in an agricultural setting were compared.…”
Section: Species At Risksupporting
confidence: 71%
“…Two small mammals considered at risk are the Great Basin pocket mouse (Perognathus parvus Peale) and the western harvest mouse (Reithrodontomys megalotis Baird) (Sullivan and Sullivan, 2008). Both species occupy big sagebrush (Artemisia tridentata Nutt.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true when one considers that success in live-trapping Western Harvest Mice may vary considerably from year to year in areas where it is known to occur (Heske et al 1984;Reynolds et al 1999*). Sullivan and Sullivan (2008) suggested that the Western Harvest Mouse could persist among habitats of diverse quality through dispersal, which is generally <300 m (Clark et al 1988;Skupski 1995). However, long-distance movements of 375-3200 m have been reported by Clark et al (1988).…”
Section: Discussionmentioning
confidence: 99%
“…Western harvest mouse (Reithrodontomys megalotis) populations are common across the western United States and central Mexico in rangeland, prairies, and deserts with elevations between -77 and 4000 m (Webster and Jones 1982;Ruff and Wilson 1999). While habitat generalists, R. megalotis populations are abundant in rangeland and old fields, as the 20 species require dense vegetative cover and tall grass for foraging, nesting, and protection from predators (Kaufman and Fleharty 1974;Sullivan and Sullivan 2008). Frequently found bordering riparian and agricultural areas and using linear habitats as corridors, the species is not sensitive to edge effects.…”
Section: Idahomentioning
confidence: 99%